Development of silk sericin extraction process using bromelain and study antioxidant activities of the hydrolysates - Thaenthanee, Suwannee; Jitpreeda, Pattamaporn; Rojpitikul, Thanawan; Subtaeng, Subongkoch (Bulletin of Applied Sciences, 2022)
Sericins, the glue-like proteins obtained from silk threads of Bombyx mori, have received many attentions in cosmetic and biomedical applications. This research aimed to study extraction process of sericins from white silk cocoon. Firstly, silk cocoon were cleaned, dried, and extracted with distilled water in an autoclave. The silk extract was digested with bromelain in 5 different levels at 1, 2, 3, 4 and 5%. After digestion, the extracts were tested for antioxidant activities by DPPH assay. It was found that the protein hydrolysate with 5% bromelain gave the highest antioxidant activities against DPPH assay with IC50 value of 7.20±0.10 mg/ml. Therefore, the bromelain concentration at 5% was chosen to digest silk extracts obtained from the 3 extraction methods, 1) extraction with distilled water in an autoclave, 2) extraction with phosphate buffer solution pH 7.0 in an autoclave and 3) extraction with 0.2% sodium hydrogen carbonate (NaHCO3) or baking soda solution and heating. Then the extracts were further digested with 5% bromelain in appropriate condition. The protein hydrolysates were collected, and the protein contents, molecular size, and antioxidant activities were measured. It was found that the protein hydrolysates had protein content of 13.00 ± 0.64, 12.32 ± 0.50 and 13.20 ± 0.95 mg/ml, respectively. Molecular size analysis using Tricine system of Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (Tricine SDS-PAGE) showed that the sizes of protein hydrolysates were smaller than that of the undigested. The antioxidants activities by DPPH assay revealed that protein hydrolysates showed significantly higher antioxidant activities than that of proteins before enzymatic digestion. It can be concluded that bromelain can enhance the antioxidant efficiency of the silk sericin extract.